Exploring Affordances of Email for Team Learning Over Time. (June 2016) - Erhardt, Niclas; Gibbs, Jennifer; Martin-Rios, Carlos; Sherblom, John
Scant research has examined the role of information and communication technologies (ICTs) for team learning across time. Drawing on theories of team learning, group development, and technological affordances, we provide a multi-method case analysis of emails and interviews that explores how and when team learning occurs. We analyze 468 emails and 20 interviews collected from a team in a large Swedish insurance company over the course of a 44-week project, from start to completion. The analysis reveals that the affordances of email (asynchronicity, editability, persistence, and replicability) and perceptions of time (time for face-to-face interaction [FtF] and time management) drive three nonlinear cycles of knowledge sharing, co-construction, and constructive conflict across the 44-week life span of the project. The findings challenge existing framings of team learning grounded in FtF contexts and highlight the increasing importance of team learning through ICTs.